PENGARUH VARIASI TEMPERATUR FURNANCE BRAZING TERHADAP SIFAT MEKANIK DALAM PEMBUATAN GRINDING ROLL MATERIAL FCD 500 DAN NI-HARD1 - Siswanto, Ari; Hanaldi , Kus; Purwadi , Wiwik; Nadi, M. Rizki Gorbyandi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This research was conducted on nodular cast iron FCD 500 and white cast iron Ni-Hard1 in the manufacturing of grinding rolls. These rolls were joined together using the furnace brazing method, with CuZn 35 filler metal placed between the two parent metals. The pressure applied in this experiment was 26,000 N using a pressure aid. The assembled parts of the grinding rolls were heated in a muffle furnace with temperature variations of 900, 950, and 1000 °C, with a holding time of 120 minutes. The results of the furnace brazing process revealed that the grinding roll sample achieved the highest shear strength at a temperature of 900 °C, with a shear strength of 6.52 MPa. The observed low shear strength is due to the penetration bonding between the metals. This was confirmed by the line analysis test, which indicated no diffusion process occurring between the metals. As the holding temperature of the brazing furnace increased, the shear strength decreased, primarily due to the melting of the CuZn 35 metal at temperatures above 900 °C, resulting in micro porosity. During the furnace brazing process, changes were observed in the microstructure of the FCD 500 parent metal. There was an increase in the amount of pearlite fraction, which in turn increased the hardness value. Additionally, the microstructure of Ni-Hard1 changed from austenite to martensite, leading to an increase in the hardness value.